The relationship between intrinsic capacity and sarcopenia in middle-aged and older Chinese populations: the mediating influence of a novel nutritional index - Ding, Hong; Li, Changqing; Zhao, Xiaojiang (Frontiers in Public Health, 2025)
BackgroundSarcopenia poses a major global health issue, with intrinsic capacity (IC) linked to its risk. This study examined the link between IC and sarcopenia in middle-aged and older Chinese individuals, focusing on the mediating role of triglycerides-total cholesterol-body weight index (TCBI), a new easy-to-calculate nutritional indicator.MethodsThe investigation utilized 2015 data from the China Health and Retirement Longitudinal Study (CHARLS), focusing on individuals aged 45 years or older. Sarcopenia was evaluated using the 2019 guidelines from the Asian Sarcopenia Working Group. After adjusting for various confounders, we employed multiple logistic regression to explore the link between IC, TCBI, and sarcopenia, and used a mediation model to evaluate TCBI’s role in the IC-sarcopenia. Subgroup analysis examined the heterogeneity among various groups.ResultsThis research encompassed a cohort of 6,554 individuals, displaying an average age of 59.4 ± 9.1 years, comprising 5,758 non-sarcopenia and 796 sarcopenia individuals. Mean IC was 5.1 ± 1.0 for non-sarcopenia group and 4.4 ± 1.2 for sarcopenia group. In the non-sarcopenia group, the median TCBI was 1446.4, and the interquartile range (IQR) was 922.3–2283.4. In the sarcopenia group, the median TCBI was 841.6, and the IQR was 584.9–1304.1. Significant differences in IC and TCBI were observed between the non-sarcopenia and sarcopenia groups (p < 0.001). Following rigorous adjustment for all covariates, IC was inversely associated with sarcopenia, and the risk of sarcopenia decreased by 15% for each unit increase in IC (OR = 0.85, 95%CI: 0.76–0.95, p = 0.004). Higher TCBI was associated with a 28% decrease in sarcopenia risk per unit increase (OR = 0.72, 95% CI: 0.58–0.90, p = 0.004). TCBI’s indirect effect on the IC-sarcopenia link was −4.91 × 10−3 (p < 0.001), explaining 12.29% of the total effect variation.ConclusionThe study found that IC is negatively correlated with sarcopenia, while TCBI is negatively correlated with sarcopenia, and TCBI mediates the relationship between IC and sarcopenia.